Cognitive-Enhancing and the Neuroprotective Propensity of Heartwood Caesalpinia sappan against D-Galactose- Induced Cognitive Impairments on Wistar Rats - Murthy, Pooja Rangenahalli Chidananda; Raghunathanaidu, Bharathi Doddla (Indian Journal of Pharmaceutical Education and Research)
Background: We suggest evaluating heartwood Caesalpinia sappan's capacity to both protect neurons and improve cognition in Wistar rats by protecting them from the cognitive deficits caused by D-galactose. Objectives: The purpose of investigation was to identify Caesalpinia sappan's neuroprotective and cognitive-enhancing effects against D-galactose-induced cognitive impairments on Wistar rats. Materials and Methods: Cognitive impairment in rats was induced by injecting 2 mg/kg of d-galactose. Wistar rats received pretreatment with 150, 250 and 500 mg/kg of Caesalpinia sappan 1 hr after the d-galactose challenge. Behavioral impairment was assessed. Oxidative status and neurotransmitter levels were evaluated. Histopathology of the brain and other organs was done. Additionally, Immunoblotting assays were performed to assess apoptosis markers. Results: Caesalpinia sappan treatment effectively reduced the cognitive impairment problem in the rats. The levels of AchE, H2O2, ROS, NO, Nos and 5-TH synthesis were effectively reduced in brain tissue and showed improved cognitive problems in rats by hydroethanolic of heartwood Caesalpinia sappan treatment. Caesalpinia sappan attenuates the free radical index and ameliorates the antioxidant index in the brains of rats. The levels of neurotransmitters were increased in Caesalpinia sappan. The results of histopathological and immunoblotting analysis demonstrated the neuroprotective effects of hydroethanolic of heartwood Caesalpinia sappan. Conclusion: According to the current findings, Caesalpinia sappan pretreatment reduced cognitive impairment in rats by acting on their neurotransmitters and antioxidant levels. Consequently, it is feasible to conclude that hydroethanolic of heartwood Caesalpinia sappan could be a useful treatment for cognitive deficits.
Keywords: Alzheimer's disease; Behavioural parameters; Caesalpinia sappan; Histopathology analysis; Immunoblotting studies; In vivo studies; Neurotransmitters.